LONG-TERM FOLLOW-UP OF THREE PATIENTS WITH PERIODIC PARALYSIS - Bonsu, Osei; Shakir, Mohamed; Hoang , Thanh (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Periodic paralysis (PP) is a disorder of muscle ion channels, often precipitated by heavy exercise, fasting or high- carbohydrate meals. CASES Case 1: A 28-year-old male with hyperthyroidism had severe lower extremity weakness progressing to the upper extremities after high-intensity exercise, with serum K 1.7 mmol/L. Examination showed normal vitals, palpable thyroid and no neurological deficit. Methimazole, propranolol and KCl wer given. KCl was discontinued after 4 weeks with normalization of serum K. He developed hypothyroidism three months later and was prescribed levothyroxine. He is currently euthyroid without recurrent PP for six years. Case 2: A 29-year-old male presented with severe exertional muscle weakness for 1.5 years. Examination showed normal vitals, thyroid, muscle and neurologic exam. Results revealed normal TFT, serum K, creatine kinase and decreased amplitude of compound muscle action potential with reduced motor unit recruitment or electrical silence on electromyography. Genetic testing found CACNA1S mutation consistent with hypokalemic PP. He was prescribed eplerenone and acetazolamide with resolution of symptoms for ten years. Case 3: A 72-year-old male presented with episodes of flaccid paralysis, occurring an hour post-dinner, with serum K 3.2 mmol/L. Symptoms resolved after taking potassium. Examination during the episode showed stage 1 hypertension, proximal muscle weakness and hyporeflexia. Results revealed normal TSH (2.03 μIU/mL) and K (4.3 mmol/L). He continued to perform normal daily activities without any PP symptoms for nine years. CONCLUSION Limited information is available regarding the long-term follow up of patients with PP. Our patients illustrate a relatively benign long-term course with appropriate treatment.